2011
DOI: 10.3727/108354210x12864727453106
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Length of Stay: A Parametric Survival Analysis

Abstract: Length of stay is one of the most important decisions made by tourists as it conditions their overall expenditure and stress caused on local resources. This article estimates survival analysis models to learn the determinants of length of stay as survival analysis naturally lends itself to study the time elapsed between arrival and departure. It is found that sociodemographic profiles, such as nationality and gender, and trip attributes, such as repeat behavior, travel motive, and type of flight, are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
5
17
1
Order By: Relevance
“…Finding an appropriate set of determinants is important for marketing policies to affect LOS, which then influences the level of revenue via higher occupancy rates and consumer spending. When considering carrying capacity calculations in sustainability studies, LOS is also an important indicator for monitoring, managing and determining the stress on local resources caused by tourism activities (Celidoni, Procidano, & Salmasi, 2010;De Menezes & Moniz, 2011;Saarinen, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finding an appropriate set of determinants is important for marketing policies to affect LOS, which then influences the level of revenue via higher occupancy rates and consumer spending. When considering carrying capacity calculations in sustainability studies, LOS is also an important indicator for monitoring, managing and determining the stress on local resources caused by tourism activities (Celidoni, Procidano, & Salmasi, 2010;De Menezes & Moniz, 2011;Saarinen, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The daily price of each of the accommodation options is the underlying factor that accounts for this highly significant impact of the different types of accommodations (Fleischer and Byk, 2009). According to Menezes and Moniz (2011), Grigolon et al (2014) or Yang and Zhang (2015), party size has been analysed from a party composition perspective. All three models signal that the greatest number of nights spent at the destination corresponds to trips accompanied by adult family members, followed by trips undertaken with friends.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in line with previous findings (Lamb et al, 2013;Litvin et al, 2004), and is explained by the higher level of confidence shown by culturally similar tourists, who develop a more positive appreciation of the tourist destination before travelling. Tourists from northern Europe (both first-time and repeat visitors) stay in the Algarve for shorter periods of time compared with those from southern Europe, again as predicted by the literature (Martínez-Garcia & Raya, 2008;Menezes & Moniz, 2011), and can be understood in terms of such tourists visiting different places from those with which they are familiar (Guillet et al, 2011;Zimmer et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The length of stay in a particular tourist destination is also affected by gender, education, and the age of tourists, with longer stays being made by tourists who are male, more educated, and older (Barros & Machado, 2010;Machado, 2010;Salmasi, Celidoni, & Procidano, 2012). Nationality also plays a role in explaining the length of stay in a tourist destination (Gokovali et al, 2007), with tourists who travel from more distant countries (particularly on the same continent) staying for shorter periods of time compared with those who travel from closer countries (Martí-nez-Garcia & Raya, 2008;Menezes & Moniz, 2011). For domestic tourists, visiting friends and relatives is a driver for travel and explains longer durations of stay compared with foreign tourists because domestic tourists usually stay in the homes of those friends and relatives, thereby avoiding accommodation costs (Kasim et al, 2013;Wang, 2005;Wang, Zhang, Xia, & Wang, 2008).…”
Section: Market Segmentation and Length Of Staymentioning
confidence: 96%